2015
DOI: 10.1001/jamaoncol.2015.2010
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With Carfilzomib-Lenalidomide-Dexamethasone With Lenalidomide Extension in Patients With Smoldering or Newly Diagnosed Multiple Myeloma

Abstract: Carfilzomib-lenalidomide-dexamethasone therapy is tolerable and demonstrates high rates of MRD negativity in NDMM, translating into longer progression-free survival in patients achieving MRD negativity. Carfilzomib-lenalidomide-dexamethasone therapy also demonstrates efficacy in high-risk SMM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
251
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 278 publications
(270 citation statements)
references
References 24 publications
14
251
3
2
Order By: Relevance
“…The results were very similar across age groups, with the oldest patient on the trial being 88 years of age, 86 and the regimen was found to be effective in individuals with high-risk disease. 99 Based on these phase II studies that did not exclude transplant ineligible patients, the NCCN panel has included carfilzomib/lenalidomide/dexamethasone as an option (category 2B) for the treatment of all patients with newly diagnosed MM, including those who are not eligible for SCT. Carfilzomib can potentially cause cardiac and pulmonary toxicities in elderly patients.…”
mentioning
confidence: 99%
“…The results were very similar across age groups, with the oldest patient on the trial being 88 years of age, 86 and the regimen was found to be effective in individuals with high-risk disease. 99 Based on these phase II studies that did not exclude transplant ineligible patients, the NCCN panel has included carfilzomib/lenalidomide/dexamethasone as an option (category 2B) for the treatment of all patients with newly diagnosed MM, including those who are not eligible for SCT. Carfilzomib can potentially cause cardiac and pulmonary toxicities in elderly patients.…”
mentioning
confidence: 99%
“…In fact, MRD negativity is consistently associated with a better PFS and overall survival. [1][2][3][4][5][6][7][8][9] In this issue of the Journal, Sherrod et al 10 publish a timely review article focusing on MRD testing after stem cell transplantation for patients with multiple myeloma. They review and discuss novel biochemical assays (including serum-free light-chain assays and heavy-chain/light-chain assays) as well as novel methods to measure MRD, including multi-parametric flow cytometry, PCR, next-generation sequencing and functional imaging modalities.…”
mentioning
confidence: 99%
“…As proposed by Sherrod et al 10 a modern study design would be to randomize patients who achieve MRD 10 − 6 negative status to upfront HDM-ASCT versus delayed HDM-ASCT; in parallel, patients who do not achieve MRD 10 − 6 negativity after a defined number of combination cycles (for example, six) could be randomized to various treatment strategies, such as immediate HDM-ASCT versus further cycles of induction until the achievement of MRD 10 − 6 followed by re-randomization to HDM-ASCT, or not. In our opinion, an MRD-driven study-built on modern combination therapy (such as carfilzomib, lenalidomide and dexamethasone) 8 -is a logical next step from where we are right now (Figure 1). …”
mentioning
confidence: 99%
“…in the "FORTE study", NCT02203643, combining carfilzomib with lenalidomide or cyclophosphamide in newly diagnosed MM patients eligible for ASCT). In a small phase II trial in newly diagnosed MM patients treated with carfilzomib-lenalidomidedexamethasone, 12-month PFS for MRDnegative vs MRD-positive status by MFC and NGS was 100% vs 79% (p<0.001) and 100% vs 95% (P = 0.02), respectively (82). Finally, to determine the ability of the new anti-CD38 MoAb daratumumab to further clear the neoplastic clone beyond CR, MRD was assessed on BM by ClonoSEQ™ NGS-based assay in two large phase III studies, CASTOR (daratumumab-bortezomib-dexamethasone versus bortezomib-dexamethasone) and POLLUX (daratumumablenalidomide-dexamethasone versus lenalidomide-dexamethasone): daratumumab in combination with standard of care significantly improved MRD-negative rates at all sensitivity thresholds, leading to a lower risk of progression in MRD-negative patients, even in high-risk subjects (83).…”
Section: Multiple Myelomamentioning
confidence: 99%